Proceedings of the 8th Conference on Human-Computer Interaction With Mobile Devices and Services 2006
DOI: 10.1145/1152215.1152266
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing locations of off-screen objects on mobile devices

Abstract: Browsing large information spaces such as maps on the limited screen of mobile devices often requires people to perform panning and zooming operations that move relevant display content offscreen. This makes it difficult to perform spatial tasks such as finding the location of Points Of Interest (POIs) in a city. Visualizing the location of off-screen objects can mitigate this problem: in this paper, we present a user study comparing the Halo [2] approach with two other techniques based on arrows.Halo surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…In reality, however, due to their large distance to a route it is still an ongoing research agenda to identify effective ways to visualize them on small screens such as mobile phones. Studies have suggested ways of visualizing off-screen landmarks (Baudisch & Rosenholtz, 2003;Burigat et al, 2006;Gustafson et al, 2008), and here we designed a visualization using the similar theory but a different presentation.…”
Section: Study 3: Visualizing Route Instructionsmentioning
confidence: 99%
“…In reality, however, due to their large distance to a route it is still an ongoing research agenda to identify effective ways to visualize them on small screens such as mobile phones. Studies have suggested ways of visualizing off-screen landmarks (Baudisch & Rosenholtz, 2003;Burigat et al, 2006;Gustafson et al, 2008), and here we designed a visualization using the similar theory but a different presentation.…”
Section: Study 3: Visualizing Route Instructionsmentioning
confidence: 99%
“…For instance, for tasks that order targets from closest to farthest, scaled arrows work better than Halos [4]. For accurate positioning Halos or Wedges are preferred over arrows [2].…”
Section: Visual Cues For Off-screen Objectsmentioning
confidence: 99%
“…Several alternative techniques for localizing off-screen objects have more recently been developed for use specifically on devices with small screens, including scaled and annotated arrows (Burigat, Chittaro, & Gabrielli, 2006), City Lights (Zellweger, Mackinlay, Good, Stefik, & Baudisch, 2003), Halo (Baudisch & Rosenholtz, 2003), and Wedge (Gustafson, Baudisch, Gutwin, & Irani, 1998). These techniques use different methods to visually encode both directional and distance information, providing compact support for off-screen object visualization.…”
Section: Hardware Constraintsmentioning
confidence: 99%
“…These techniques use different methods to visually encode both directional and distance information, providing compact support for off-screen object visualization. Whereas user studies (Baudisch & Rosenholtz, 2003;Burigat et al, 2006;Gustafson et al, 2008) have shown the competing advantages of different techniques for off-screen object visualization, no evaluation has, to our knowledge, been made of their application for user awareness in mobile shared workspaces.…”
Section: Hardware Constraintsmentioning
confidence: 99%